Dynamical Soliton Solutions of (2+1)-Dimensional Paraxial Wave and (4+1)-Dimensional Fokas Wave Equations With Truncated M-Fractional Derivative Using an Efficient Technique - Bulut, Hasan; Demirbilek, Ulviye; Celik, Ercan (Wiley, 2025)
The main aim of this paper is to use the modified generalized Kudryashov technique to accurately represent the traveling wave solutions for (2 + 1)-dimensional paraxial and (4 + 1)-dimensional Fokas wave equations with truncated M-fractional derivative. Symbolic computation is utilized to present soliton solutions with different physical properties and specific parameters. Additionally, visual representations such as 3-dimensional, 2-dimensional, contour, and density surfaces are provided for some of the reported data. The effectiveness of the modified generalized Kudryashov approach is demonstrated by the findings presented in this paper.
Keywords: Fokas wave equation; modified generalized Kudryashov technique; paraxial wave equation; soliton solutions; truncated M-fractional derivative